Analisis Sistem Informasi Akuntansi Badan Layanan Umum Daerah - Gita Jumaida Panjaitan; Dian Hakip Nurdiansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the weaknesses and strengths of the accounting information system for the Regional Public Service Agency at the Tirtamulya Health Center. Tirtamulya Health Center is a community health service located in Cikampek, Karawang. As technology develops, of course there are many information systems that are used, one of which is the accounting information system used by the Regional Public Service Agency, especially the Tirtamulya Health Center which aims to assist in accounting and financial processes. The Puskesmas manages operational funds originating from the government and of course must be accountable back to the government regarding incoming and outgoing funds. Of course, with operational funds originating from the government and the funds provided are quite large, an information system is needed that is specifically designed to manage operational funds. As technology develops, of course there are many information systems that are used, one of which is the accounting information system used by the Regional Public Service Agency, especially the Tirtamulya Health Center which aims to assist in accounting and financial processes. Accounting information systems certainly have some advantages and disadvantages depending on each system. Therefore, this study analyzes the Accounting Information System by means of field studies in the form of direct observation. Keywords: Accounting Information System, Financial, BLUD.